Simulating the Temporal and Spatial Patterns of Urban Growth in Abha Using the Markov-CA Combined Statistical Model During the Period from 2000 to 2040 - Alqahtani, Eman Mohammed Ali (Journal of Humanities & Social Sciences, 2025)
The use of spatial and temporal analysis in studies related to urbanization is one of the most important modern trends in urban studies. This approach relies on modeling and simulation to predict the future, with the integrated statistical model (Markov) being one of the most significant and widely used models for this purpose. This research aims to study the stages of urban growth in the city of Abha, predicting potential future developments to achieve a stable vision. The study utilizes geographic information systems (GIS) and remote sensing techniques to detect spatial and temporal changes in urban masses, track urban growth patterns, identify directions, and determine influencing factors. It also forecasts potential urban changes in the study area up to the year 2040. To achieve these objectives, the study relies on Landsat satellite imagery for the years 2000, 2010, and 2020. These images are processed and subjected to supervised classification to extract urban masses in the study area over the period from 2000 to 2020. The study results indicate that the city of Abha has experienced significant urban expansion in recent years, with the urban area increasing from 26.6 km² in 2000 to 38.4 km² in 2010, reaching 69 km² in 2020. This expansion occurred primarily at the expense of desert lands near the city center.